2022
DOI: 10.3390/cancers14051170
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immune Response Assessment in Colon Cancer by Immunoscore (Automated Digital Pathology) and Pathologist Visual Scoring

Abstract: Adjunction of immune response into the TNM classification system improves the prediction of colon cancer (CC) prognosis. However, immune response measurements have not been used as robust biomarkers of pathology in clinical practice until the introduction of Immunoscore (IS), a standardized assay based on automated artificial intelligence assisted digital pathology. The strong prognostic impact of the immune response, as assessed by IS, has been widely validated and IS can help to refine treatment decision mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…LN staging in contemporary clinical practice is binary; nodes are either infiltrated with cancer or not. This study, along with previous work on the prognostic value of looking at immune compartments in pathological samples, suggests that LN infiltration represents a spectrum of disease (Boquet et al., 2022; Galon et al., 2012; Pagès et al., 2018).…”
Section: Discussionsupporting
confidence: 69%
“…LN staging in contemporary clinical practice is binary; nodes are either infiltrated with cancer or not. This study, along with previous work on the prognostic value of looking at immune compartments in pathological samples, suggests that LN infiltration represents a spectrum of disease (Boquet et al., 2022; Galon et al., 2012; Pagès et al., 2018).…”
Section: Discussionsupporting
confidence: 69%
“…LN staging in contemporary clinical practice is binary; nodes are either infiltrated with cancer or not. This study, along with previous work on the prognostic profundity of looking art immune compartment in pathological samples, suggests LN infiltration represents a spectrum of disease [78][79][80] .…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, a weak concordance was previously reported between pathologist visual scoring of the CD3+ and CD8+ T-cell densities at the tumor site and Immunoscore for early-stage colon cancer and minimal agreement among pathologists was observed. 36 However, whether a digital assessment might better quantify TILs leading to a more suitable evaluation of their predictive value for ICIs efficacy in mCRC remains to be established. To this regard, a recent retrospective study showed that a machine learning-based analysis of H&E digital images of patients with metastatic NSCLC treated with single-agent ICIs found a higher response rates and longer PFS and OS in tumors with higher levels of TILs.…”
Section: Discussionmentioning
confidence: 99%